Use of black soldier fly larvae composter bin to reduce household food waste - Awang, Zarizi; Imran, Wan Muhammad; Tajul Baharuddin, Mohamad Faizal; Hashim, Nor Haslina; Hamidon, Nuramidah; Mohd Arish, Nur Aini (Penerbit UTHM, 2020)
Food waste is the largest component in municipal solid waste (MSW). About 1.3 billion tons of food, which is equivalent to one third of global food production is lost or wasted every year along the food supply chain [1]. In Malaysia, total generation of MSW is 15,000 tons. This MSW consists of 50% food waste, of which 70% is disposed at the landfill sites [2]. It was reported that in average a household in Malaysia throw away around 0.5-0.8 kg uneaten food per day [3]. This food waste is recognized as huge problem worldwide and it becomes particularly severe to developing country. There are many methods that can be carried out to reduce the food waste generation. Composting method is one of the methods to convert food waste into valuable product with minimum cost.